Pengaruh Perubahan Iklim terhadap Hujan Rencana pada DAS Ciliwung, DKI Jakarta - Andi Mukti Widayanto; Endah Kurniyaningrum (Syntax Literate, 2023)
Climate change is inevitable due to global warming and is believed to have a broad impact on various aspects of life. Therefore, it is necessary to conduct an analysis to find out how the study of the effect of climate change on rainfall plans and flood discharge designed by the Ciliwung watershed in the DKI Jakarta provincial area. Based on the results of the analysis of historical rain data, it can be seen that there is an increase and decrease in rainfall in certain periods. Based on the results of the analysis of water availability in all periods, it shows that the availability of water in the Ciliwung watershed tends to fluctuate from year to year. Based on the results of the planned rainfall analysis, it was found that the average change in planned rainfall per year from 1993 to 2042 was 1.29%. Based on the results of the planned flood discharge analysis, it was found that the average change in planned flood discharge per year from 1993 to 2042 was 5.30%. Overall, climate change has a significant influence on the Ciliwung watershed area, especially in DKI Jakarta.